Development, validation and operating room-transfer of a six-step laparoscopic training program for the vesicourethral anastomosis - Klein, Jan; Teber, Dogu; Frede, Thomas; Stock, Christian; Fiedler, Marcel; Gözen, Ali Serdar; Seemann, Othmar; Schulze, Michael; Rassweiler, Jens (Journal of endourology, 2013)
Purpose: Development and full validation of a laparoscopic training program for stepwise learning of a reproducible application of a standardized laparoscopic anastomosis technique and integration into the clinical course.Materials and Methods: The training of vesicourethral anastomosis (VUA) was divided into six simple standardized steps. To fix the objective criteria, four experienced surgeons performed the stepwise training protocol. Thirty-eight participants with no previous laparoscopic experience were investigated in their training performance. The times needed to manage each training step and the total training time were recorded. The integration into the clinical course was investigated. The training results and the corresponding steps during laparoscopic radical prostatectomy (LRP) were analyzed. Data analysis of corresponding operating room (OR) sections of 793 LRP was performed. Based on the validity, criteria were determined.Results: In the laboratory section, a significant reduction of OR time for every step was seen in all participants. Coordination: 62%; longitudinal incision: 52%; inverted U-shape incision: 43%; plexus: 47%. Anastomosis catheter model: 38%. VUA: 38%. The laboratory section required a total time of 29 hours (minimum: 16 hours; maximum: 42 hours). All participants had shorter execution times in the laboratory than under real conditions. The best match was found within the VUA model. To perform an anastomosis under real conditions, 25% more time was needed. By using the training protocol, the performance of the VUA is comparable to that of an surgeon with experience of about 50 laparoscopic VUA. Data analysis proved content, construct, and prognostic validity.Conclusions: The use of stepwise training approaches enables a surgeon to learn and reproduce complex reconstructive surgical tasks: eg, the VUA in a safe environment. The validity of the designed system is given at all levels and should be used as a standard in the clinical surgical training in laparoscopic reconstructive urology.
Gesehen am 09.06.2022